Skrining Bakteri Lipolitik Hasil Isolasi dari Tanah Terkontaminasi Minyak - Khurniyati, Maylina Ilhami; Sumarsih, Sri; Chasanah, Uswatun (ALKIMIA, 2022)
Lipase (triasilglycerol acylhydrolase, E.C, 3.1.1.3) is an enzyme can hydrolyze long chains of triglycerides[1]. Lipase is a water-soluble enzyme and naturally lipase catalyze the hydrolysis of ester bonds in water insoluble lipid substrate and long-chain acylglycerol synthesis, diacylglycerol, monoacylglycerol, and glycerol[2]. Hydrolase enzyme lipase can be used potentialy produced fatty acid which precursors in the chemical industry[3]. The research aims to study the lipolytic activity of bacteria isolated from soil contaminated with oil. Screening of lipolytic bacteria was performed in Rhodamin-B agar plate containing olive oil. The lipolytic activity was determined by spectrofotometry method toward p-nitrofenil palmitat as a substrate. The result this research showed that there are 15 of 150 isolates bacteria from soil contaminated with oil was confirmed by observing the zone of hydrolysis formed around the growth of colony on Rhodamin B agar plate containing olive oil. One of the lipolytic bacteria identified as higher activity was produced lipase with activity of 7,41 U/ml